Pengaruh Praktik Green Human Resource Management Terhadap Turnover Pegawai Dimediasi Lingkungan Kerja pada Bank BRI Cabang Gorontalo - Ridwan Nur Bahri Miolo; Robiyati Podungge; Rezkiawan Tantawi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to determine the effect of Green Human Resource Management Practices on Employee Turnover Mediated by the Work Environment at Bank BRI Gorontalo Branch. The population of this research is contract employees at Bank BRI Gorontalo Branch. The sampling technique taken in this research uses an incidental technique, the number of samples is taken in research using the Slovin formula, namely 66 respondents. Data collection techniques in this research used observation, questionnaires, interviews and documentation. The analytical test tool used in testing this research is multiple linear regression. The data analysis method uses the SPSS 22 application. The results of this research show that, (1) Green Human Resources cannot have a significant effect on Employee Turnover at Bank BRI Gorontalo Branch, (2) Green Human Resources can have a significant effect on the Work Environment at Bank BRI Gorontalo Branch , (3) The Work Environment can have a significant effect on Employee Turnover at Bank BRI Gorontalo Branch, (4) The Work Environment can mediate the influence of Green Human Resources on Employee Turnover at Bank BRI Gorontalo Branch.